"Installation art"-like hierarchical self-assembly of giant polymeric elliptical platelets. Issue 6 (27th January 2017) - Huang, Lei; Lei, Zuotao; Huang, Tong; Zhou, Yongfeng; Bai, Yongping
Abstract : This paper reports a novel "installation art"-like hierarchical self-assembly process of amphiphilic polyamides into giant and complex structures such as elliptical platelets, six-horned, starfish-like and flower-like superstructures. Abstract : This paper reports the aqueous self-assembly of giant elliptical platelets over 20 μm in axial length, from a novel polyamide. Both the self-assembly pathway and mechanism were studied using morphology and X-ray characterizations. The polymer first self-organizes into small quadrangular frustum pyramid platelets, and then these small platelets can be further installed into giant elliptical platelets through an "installation art"-like hierarchical self-assembly process driven by crystallization. The as-prepared regular giant platelets can further aggregate together into multi-horned or flower-like superstructures.